Preparation method of multiband photoelectric compatible absorbing material based on dysprosium-doped garnet ferrite

By combining hydrothermal synthesis with solid-state reaction, rare earth element Dy3+ doped garnet ferrite materials have achieved cross-spectral synergistic response, solving the problem of multi-band optoelectronic compatibility absorption of existing materials under complex electromagnetic and optical environments. They also exhibit excellent magnetoelectric synergistic loss performance and wide-range near-infrared absorption characteristics.

CN121470941APending Publication Date: 2026-02-06NAT UNIV OF DEFENSE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511862970.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-07-01
Filing Date
2025-12-11
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing materials are difficult to achieve cross-spectral synergistic response in complex electromagnetic and optical environments, and single-functional materials are difficult to meet the requirements of multi-band optoelectronic compatible absorption.

Method used

A preparation strategy combining hydrothermal synthesis and solid-state reaction was adopted. By doping with rare earth element Dy3+ and combining it with ferrite lattice control, dysprosium-doped garnet ferrite materials were prepared to achieve cross-spectral synergistic response.

Benefits of technology

It achieves microwave-dual-laser-visible light compatible absorption, breaking through the technical limitations of traditional heterostructures, and provides a theoretical framework and experimental paradigm for the preparation and engineering application of next-generation multi-band compatible absorption materials. It has excellent magnetoelectric synergistic loss performance and wide-range near-infrared absorption characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121470941A_ABST
    Figure CN121470941A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multiband photoelectric compatible absorbing material based on dysprosium-doped garnet ferrite, and belongs to the technical field of photoelectric functional materials. The invention aims to solve the problems that an existing material with a single function is difficult to meet performance requirements in complex electromagnetic and optical environments, and cross-spectrum collaborative response is difficult to realize. According to the invention, the f-f transition characteristic of Dy < 3 + > is combined with the lattice regulation and control of garnet ferrite, so that magnetoelectric synergistic loss is realized; the magnetic moment density of the material is remarkably improved through the high spin-orbit coupling effect of Dy < 3 + >, meanwhile, a specific laser echo signal can be effectively restrained through a wide-area near-infrared absorption band of the material, and ferrite serves as a carrier and a chromaticity regulator. The invention realizes the multiband compatible absorption effect, and is suitable for electromagnetic absorption, optical protection and environment fusion scenes, such as the fields of intelligent optical coatings and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optoelectronic functional materials technology, specifically relating to a method for preparing multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite. Background Technology

[0002] With the rapid development of high-frequency electronic equipment, single-function materials are insufficient to meet the performance requirements under complex electromagnetic and optical environments. Although traditional materials such as spinel ferrite and yttrium iron garnet single crystals have functional characteristics in specific frequency bands, their designs are mostly limited to single performance optimization (such as magnetic loss or dielectric modulation), making it difficult to achieve cross-spectral synergistic response.

[0003] Garnet ferrites, with their multi-physics coupling effect, high-frequency magnetic loss capability, and structural stability, have become an important carrier for research on optoelectronic compatible absorption materials. Recent studies have shown that rare-earth-ferrite composite systems can be used for photoelectric absorption: for example, Ding et al. based Sm... 3+ The upconversion properties of SmNi prepared by solid-state reaction x Fe 1-x O3 exhibits significant low laser reflection in the 1.06 μm wavelength band. Other studies have demonstrated this effect using La... 3+ By replacing the lattice sites of Ca2Fe2O5 and enhancing interfacial polarization loss using the sol-gel method, a wide-range microwave absorption performance was achieved; while Yu et al. prepared a planar hexagonal Ba3Co2Fe 24- x Dy x O 41 The system achieves synergistic optimization of thinness and wide absorption band at specific doping ratios. However, most studies focus on absorption in a single wavelength band, and there are few reports on using this material system for multi-band optoelectronic compatible absorption. Summary of the Invention

[0004] The purpose of this invention is to address the problem that existing single-function materials are unable to meet the performance requirements of complex electromagnetic and optical environments and are difficult to achieve cross-spectral synergistic response, and to provide a method for preparing multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite.

[0005] A method for preparing a multi-band optoelectronic compatible absorption material based on dysprosium-doped garnet ferrite is specifically carried out according to the following steps:

[0006] I. Preparation of spherical Dy2O3 powder:

[0007] ① Dissolve Dy(NO3)3·5H2O in ethylene glycol and stir at a constant temperature until a homogeneous solution is formed. Then add CH3COONa and stir until completely dissolved. Adjust the pH of the solution to alkaline to obtain the precursor mixture.

[0008] ② The precursor mixture is transferred to a high-pressure reactor and subjected to hydrothermal reaction at 170℃~180℃. After the reaction is completed, the reaction product is washed and vacuum dried to obtain spherical Dy2O3 powder.

[0009] II. Preparation of Dy by High-Temperature Solid-State Method x Fe 2-x O3:

[0010] ① Add spherical Dy2O3 powder and Fe2O3 powder to a ball mill jar at a certain mass ratio, then add deionized water, ball mill for a period of time, and then transfer to a constant temperature forced air drying oven to dry to obtain mixed powder;

[0011] ② The mixed powder is loaded into a ceramic crucible, which is then placed in a tube furnace and heated to 1100℃~1300℃ in an Ar atmosphere. The mixture is then calcined for a period of time in an Ar atmosphere at 1100℃~1300℃. Finally, it is ground to obtain a dysprosium-doped garnet ferrite composite material.

[0012] The principle of this invention:

[0013] I. This invention utilizes a synergistic preparation strategy combining hydrothermal synthesis and solid-state reaction to control rare-earth doping concentration. By combining the electronic transition characteristics of rare-earth elements with ferrite lattice modulation, it achieves performance optimization through cross-spectral synergistic response. Research shows that Dy 3+ The ff transition can form a wide-range near-infrared absorption band, and its strong spin-orbit coupling effect can significantly improve the magnetic moment density and high-frequency magnetic loss performance of ferrite, providing a physical basis for multi-spectral synergistic control. This invention achieves microwave-dual-laser-visible light compatible absorption in a rare earth-ferrite material system for the first time, breaking through the technical limitations of traditional heterostructures and providing a theoretical framework and experimental paradigm for the preparation and engineering application of a new generation of multi-band compatible absorption materials.

[0014] Advantages of this invention:

[0015] I. Rare Earth-Ferrite Synergistic Regulation Mechanism: This invention utilizes Dy 3+ The ff transition characteristics are combined with the lattice modulation of garnet ferrite to achieve magnetoelectric synergistic loss; Dy 3+ The high spin-orbit coupling effect significantly improves the magnetic moment density of the material, while its wide-range near-infrared absorption band can effectively suppress specific laser echo signals. Ferrite acts as a carrier and color modifier.

[0016] II. Hydrothermal-solid phase synergistic preparation process: This invention adopts a synergistic strategy of hydrothermal synthesis pre-regulating grain morphology and solid phase reaction doping concentration gradient to achieve microwave band performance enhancement and visible light band chromaticity control.

[0017] III. Multi-band optoelectronic compatibility absorption performance: This invention achieves multi-band compatible absorption effects: microwave absorption (reflection loss of -16.24dB at a thickness of 3.3mm, and effective bandwidth of 3.11GHz at a thickness of 3.4mm), laser absorption (diffuse reflectance of 14.3% at a thickness of 1.06μm and 17.2% at a thickness of 1.54μm), and visible light environment fusion (CIE-Lab chromatic aberration of 2.16), without relying on multi-layer composite structures, providing a new paradigm for the design of lightweight absorption materials in complex electromagnetic-optical environments;

[0018] IV. The multi-band optoelectronic compatible absorption material based on dysprosium-doped garnet ferrite prepared by this invention is suitable for electromagnetic absorption, optical protection and environmental integration scenarios, such as smart optical coatings. Attached Figure Description

[0019] Figure 1 The images show the XRD patterns of the multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3.

[0020] Figure 2 The middle left figure shows the diffuse reflectance of the multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3 at 400-1800 nm. Figure 2 The right-middle figure shows the reflectance of the multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3 at 1064 nm and 1540 nm.

[0021] Figure 3 The figures show the three-dimensional and two-dimensional reflection loss distributions of the multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3. The left figure is Example 1, the middle figure is Example 2, and the right figure is Example 3.

[0022] Figure 4 The left image shows the chromaticity coordinates of the multi-band opto-compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3, and the right image shows a photograph of the actual multi-band opto-compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3. Detailed Implementation

[0023] Specific Implementation Method 1: This implementation method describes a preparation method for a multi-band optoelectronic compatible absorption material based on dysprosium-doped garnet ferrite, which is specifically completed according to the following steps:

[0024] I. Preparation of spherical Dy2O3 powder:

[0025] ① Dissolve Dy(NO3)3·5H2O in ethylene glycol and stir at a constant temperature until a homogeneous solution is formed. Then add CH3COONa and stir until completely dissolved. Adjust the pH of the solution to alkaline to obtain the precursor mixture.

[0026] ② The precursor mixture is transferred to a high-pressure reactor and subjected to hydrothermal reaction at 170℃~180℃. After the reaction is completed, the reaction product is washed and vacuum dried to obtain spherical Dy2O3 powder.

[0027] II. Preparation of Dy by High-Temperature Solid-State Method x Fe 2-x O3:

[0028] ① Add spherical Dy2O3 powder and Fe2O3 powder to a ball mill jar at a certain mass ratio, then add deionized water, ball mill for a period of time, and then transfer to a constant temperature forced air drying oven to dry to obtain mixed powder;

[0029] ② The mixed powder is loaded into a ceramic crucible, which is then placed in a tube furnace and heated to 1100℃~1300℃ in an Ar atmosphere. The crucible is then calcined for a period of time in an Ar atmosphere at 1100℃~1300℃. Finally, it is ground to obtain a multi-band optoelectronic compatible absorption material based on dysprosium-doped garnet ferrite.

[0030] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the mass ratio of Dy(NO3)3·5H2O to the volume ratio of ethylene glycol in step one ① is (2g~3g):40mL. The other steps are the same as in Specific Implementation Method One.

[0031] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that the temperature of the constant-temperature stirring in step one ① is 50℃~70℃. The other steps are the same as in Specific Implementation Method One or Two.

[0032] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that: the mass ratio of CH3COONa to ethylene glycol in step one ① is (2g~4g):40mL; and ammonia is used in step one ① to adjust the pH of the solution to 8. Other steps are the same as in Specific Implementation Methods One to Three.

[0033] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the hydrothermal reaction time described in step one, step two, is 5 to 7 hours. The other steps are the same as in Specific Implementation Methods One to Four.

[0034] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that: the washing described in step one ② involves alternating washing of the reaction product with anhydrous ethanol and deionized water, with each solvent washing 3 to 5 times; the vacuum drying temperature described in step one ② is 50℃ to 70℃, and the vacuum drying time is 10 to 12 hours. Other steps are the same as in Specific Implementation Methods One to Five.

[0035] Specific Implementation Method Seven: The difference between this implementation method and Specific Implementation Methods One to Six is ​​that the mass ratio of the spherical Dy2O3 powder to the Fe2O3 powder in step two① is 1:(1~2). The other steps are the same as in Specific Implementation Methods One to Six.

[0036] Specific Implementation Method Eight: The difference between this implementation method and Specific Implementation Methods One to Seven is that the total mass ratio of the spherical Dy2O3 powder and Fe2O3 powder to the volume ratio of deionized water in step two① is (1g~1.2g):40mL. The other steps are the same as in Specific Implementation Methods One to Seven.

[0037] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that: in step two①, the grinding medium in the ball milling process is zirconia balls, the ball-to-material ratio is 2:1, the ball milling speed is 300 r / min to 500 r / min, and the ball milling time is 2 h to 3 h; the drying temperature in step two① is 100℃, and the drying time is 10 h to 12 h. Other steps are the same as in Specific Implementation Methods One to Eight.

[0038] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Methods One to Nine in that: the heating rate in step two ② is 5℃ / min to 10℃ / min; the calcination time in step two ② is 2h to 3h. The other steps are the same as in Specific Implementation Methods One to Nine.

[0039] The beneficial effects of the present invention are verified using the following embodiments:

[0040] Example 1: A method for preparing a multi-band optoelectronic compatible absorption material based on dysprosium-doped garnet ferrite, characterized in that the preparation method is specifically carried out according to the following steps:

[0041] I. Preparation of spherical Dy2O3 powder:

[0042] ① Dissolve 2.75g Dy(NO3)3·5H2O in 40mL ethylene glycol and stir at 60℃ until a homogeneous solution is formed. Then add 3.0g CH3COONa and stir until completely dissolved. Adjust the pH of the solution to 8 using ammonia water to obtain the precursor mixture.

[0043] ② The precursor mixture was transferred to a high-pressure reactor and subjected to hydrothermal reaction at 180°C for 6 hours. High temperature and high pressure were used to promote crystal nucleation and growth. After the reaction was completed, the reaction product was washed with anhydrous ethanol and deionized water alternately. The two solvents were used to wash the product three times each. Then, the product was vacuum dried at 60°C for 12 hours to obtain spherical Dy2O3 powder.

[0044] II. Preparation of Dy by High-Temperature Solid-State Method x Fe 2-x O3:

[0045] ① Add spherical Dy2O3 powder and Fe2O3 powder to a ball mill jar at a certain mass ratio, then add deionized water, ball mill for a period of time, and then transfer to a constant temperature forced air drying oven to dry to obtain mixed powder;

[0046] The mass ratio of spherical Dy2O3 powder to Fe2O3 powder mentioned in step 2① is 1:1.5;

[0047] The total mass ratio of the spherical Dy2O3 powder and Fe2O3 powder to the volume of deionized water in step 2① is 1g:40mL.

[0048] In step 2①, the grinding media is zirconia balls, the ball-to-material ratio is 2:1, the ball milling speed is 300 r / min, and the ball milling time is 2 h; the drying temperature in step 2① is 100℃, and the drying time is 12 h.

[0049] ② The mixed powder is loaded into a ceramic crucible, which is then placed in a tube furnace and heated to 1200℃ under an Ar atmosphere. The crucible is then calcined for 2 hours under an Ar atmosphere and at 1200℃ to promote lattice reconstruction and solid-phase reaction. Finally, it is ground to obtain a multi-band optoelectronic compatible absorption material based on dysprosium-doped garnet ferrite (denoted as DF1).

[0050] Example 2: The difference between this example and Example 1 is that the mass ratio of spherical Dy2O3 powder to Fe2O3 powder in step 2① is 1:1.75; the multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite obtained in step 2② is denoted as DF2. All other steps and parameters are the same as in Example 1.

[0051] Example 3: The difference between this example and Example 1 is that the mass ratio of spherical Dy2O3 powder to Fe2O3 powder in step 2① is 1:2; the multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite obtained in step 2② is denoted as DF3. Other steps and parameters are the same as in Example 1.

[0052] Figure 1The images show the XRD patterns of the multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3.

[0053] from Figure 1 It can be seen that all three samples exhibit strong characteristic peaks at 2θ = 25.908°, 32.246°, 33.046°, 35.421°, and 53.202°, ​​and these peaks correspond to the substances on the two PDF standard cards, proving that Fe5Dy3O 12 Successful synthesis of / DyFeO3 composite material.

[0054] Figure 2 The middle left figure shows the diffuse reflectance of the multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3 at 400-1800 nm. Figure 2 The right-middle figure shows the reflectance of the multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3 at 1064 nm and 1540 nm.

[0055] from Figure 2 It can be seen that the reflectivity variation trend of the multi-band opto-compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3 is basically consistent with the full-band reflectivity characteristics of 400-1800nm ​​in the two target bands. Moreover, significant reflection valleys are shown at 900nm, 1100nm and 1300nm in the near-infrared region. The prepared composite materials exhibit excellent laser absorption performance in the dual bands of 1064nm and 1540nm.

[0056] Figure 3 The figures show the three-dimensional and two-dimensional reflection loss distributions of the multi-band optoelectronic compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3. The left figure is Example 1, the middle figure is Example 2, and the right figure is Example 3.

[0057] from Figure 3 It can be seen that as the DFR ratio increases, the absorption performance of the sample shows a trend of first increasing and then decreasing, and the absorption peaks of the material show a merging phenomenon. Among them, DF2 has the best overall performance, with its minimum reflection loss (RLmin) reaching -14.54dB. At a thickness of 3.4mm, the effective absorption bandwidth (EAB) extends to 3.11GHz.

[0058] Figure 4 The left image shows the chromaticity coordinates of the multi-band opto-compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3, and the right image shows a photograph of the actual multi-band opto-compatible absorption materials based on dysprosium-doped garnet ferrite prepared in Examples 1-3.

[0059] Figure 4The left-middle figure shows the color characterization of composite materials based on their reflectance spectral characteristics, using the CIE 1931 XYZ standard colorimetric system. Under D65 standard light source and 2° standard observer conditions, the normalized reflectance spectrum was integrated to obtain tristimulus values ​​(X, Y, Z), which were then used to calculate the chromaticity coordinates. The color difference between the composite material and the standard brown earth color BE0922 (L∗=35.6, a∗=4.84, b∗=12.04) was compared. The results show that the color difference values ​​of samples DF1 (ΔE=3.54), DF2 (ΔE=2.16), and DF3 (ΔE=3.01) are all below or close to the human eye's discrimination threshold of 3.0, meeting the relevant technical indicators (ΔE≤3.0) in GJB 7928-2012 "General Requirements for Camouflage Coatings," indicating potential for compatible absorption with visible light.

Claims

1. A method for preparing a multi-band optoelectronic compatible absorption material based on dysprosium-doped garnet ferrite, characterized in that... The preparation method is specifically carried out according to the following steps: I. Preparation of spherical Dy2O3 powder: ① Dissolve Dy(NO3)3·5H2O in ethylene glycol and stir at a constant temperature until a homogeneous solution is formed. Then add CH3COONa and stir until completely dissolved. Adjust the pH of the solution to alkaline to obtain the precursor mixture. ② The precursor mixture is transferred to a high-pressure reactor and subjected to hydrothermal reaction at 170℃~180℃. After the reaction is completed, the reaction product is washed and vacuum dried to obtain spherical Dy2O3 powder. II. Preparation of Dy by High-Temperature Solid-State Method x Fe 2-x O3: ① Add spherical Dy2O3 powder and Fe2O3 powder to a ball mill jar at a certain mass ratio, then add deionized water, ball mill for a period of time, and then transfer to a constant temperature forced air drying oven to dry to obtain mixed powder; ② The mixed powder is loaded into a ceramic crucible, which is then placed in a tube furnace and heated to 1100℃~1300℃ in an Ar atmosphere. The crucible is then calcined for a period of time in an Ar atmosphere at 1100℃~1300℃. Finally, it is ground to obtain a multi-band optoelectronic compatible absorption material based on dysprosium-doped garnet ferrite.

2. The method for preparing a multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite according to claim 1, characterized in that... The mass ratio of Dy(NO3)3·5H2O to the volume ratio of ethylene glycol in step 1① is (2g~3g):40mL.

3. The method for preparing a multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite according to claim 1, characterized in that... The temperature of the constant temperature stirring mentioned in step 1① is 50℃~70℃.

4. The method for preparing a multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite according to claim 1, characterized in that... In step 1①, the mass ratio of CH3COONa to ethylene glycol is (2g~4g):40mL; in step 1①, ammonia is used to adjust the pH of the solution to 8.

5. The method for preparing a multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite according to claim 1, characterized in that... The hydrothermal reaction time described in step 1② is 5h~7h.

6. The method for preparing a multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite according to claim 1, characterized in that... The washing described in step 1② involves washing the reaction product alternately with anhydrous ethanol and deionized water, with each solvent washing 3 to 5 times. The vacuum drying temperature described in step 1② is 50℃ to 70℃, and the vacuum drying time is 10h to 12h.

7. The method for preparing a multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite according to claim 1, characterized in that... The mass ratio of spherical Dy2O3 powder to Fe2O3 powder in step 2① is 1:(1~2).

8. The method for preparing a multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite according to claim 1, characterized in that... The total mass ratio of the spherical Dy2O3 powder and Fe2O3 powder to the volume ratio of deionized water in step 2① is (1g~1.2g):40mL.

9. The method for preparing a multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite according to claim 1, characterized in that... In step 2①, the grinding media is zirconia balls, the ball-to-material ratio is 2:1, the ball milling speed is 300 r / min to 500 r / min, and the ball milling time is 2 h to 3 h; the drying temperature in step 2① is 100℃, and the drying time is 10 h to 12 h.

10. The method for preparing a multi-band opto-compatible absorption material based on dysprosium-doped garnet ferrite according to claim 1, characterized in that... The heating rate mentioned in step 2② is 5℃ / min~10℃ / min; the calcination time mentioned in step 2② is 2h~3h.